VOLATILES IN SILICATE MELTS AT HIGH PRESSURE AND TEMPERATURE. 1. INTERACTION BETWEEN OH GROUPS AND SI4+, AL3+, CA2+, NA+ AND H+ - Mysen B.O.; Virgo D. (My University, 1986)
Abstract The structure of silicate melts on the joins SiO 2 -H 2 O, SiO 2 -Al(OH) 3 , SiO 2 -Ca(OH) 2 and SiO 2 -NaOH at high pressure and temperature has been determined with Raman spectroscopy (quenched from 1550°C at ∼ 500°C s −1 at 15 kbar). In SiO 2 -H 2 O and SiO 2 -Al(OH) 3 melt compositions, H 2 O exists as molecular H 2 O ((H 2 O) 0 ) and as OH bonded to Si 4+ in the water concentration range between 4 and 10 wt.%. In SiO 2 -Al(OH) 3 composition melts, OH groups are also attached to Al 3+ . In the systems SiO 2 -Ca(OH) 2 and SiO 2 -NaOH, water is dissolved as sodium and calcium hydroxyl complexes in addition to molecular water. Hydroxylation of the silica tetrahedra was not observed in quenched melts along the latter two joins. On the basis of calculated free energies of hydroxylation, the relative stabilities of the hydroxyl complexes are Si … OH > Na … OH > Al … OH > Ca … OH. Nonbridging oxygen is observed in all but SiO 2 -H 2 O melts. In all systems, intensity relationships among the relevant Raman bands show increasing abundance of metal hydroxyl complexes, nonbridging oxygen and H 2 O with increasing water content.